Criminal Liability And Law Enforcement Effectiveness Against Sound Horeg Organizers Causing Public Order Disturbances, Physical Harm, Loss of Life, and Ecosystem Damage - Raka Anugrah Valentino Erlangga; Widhi Cahyo Nugroho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of audio technology has popularized the use of high-volume sound systems known as